2008
DOI: 10.1002/jssc.200800230
|View full text |Cite
|
Sign up to set email alerts
|

Detection of N‐nitroso‐bile acids at 285 nm in reverse‐phase HPLC

Abstract: In the present study, we developed a novel, simple, and specific detection method using an RP-HPLC at UV 285 nm for the separation and quantification of N-nitroso-bile acids. First, we found that N-nitroso-bile acids have a specific spectrophotometric absorbance at 285 nm. Using this 285 nm detection system, we could especially measure N-nitroso-bile acids, even in co-existence of non-N-nitroso-bile acids. Next, we observed the decomposition of N-nitroso-glychocholate under alkaline, acidic, and neutral condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…DNA adducts originating from N ‐nitroso‐bile acids have also been detected in the glandular stomach from our gastric cancer model . Furthermore, N ‐nitroso‐bile acids reportedly stabilize under acidic conditions . These findings suggest that N ‐nitroso‐bile acids appear to be involved in the occurrence of EAC from Barrett's esophagus in patients with healthy acid‐secreting stomachs.…”
Section: Barrett's Carcinogensissupporting
confidence: 60%
See 1 more Smart Citation
“…DNA adducts originating from N ‐nitroso‐bile acids have also been detected in the glandular stomach from our gastric cancer model . Furthermore, N ‐nitroso‐bile acids reportedly stabilize under acidic conditions . These findings suggest that N ‐nitroso‐bile acids appear to be involved in the occurrence of EAC from Barrett's esophagus in patients with healthy acid‐secreting stomachs.…”
Section: Barrett's Carcinogensissupporting
confidence: 60%
“…117,118 Furthermore, N-nitroso-bile acids reportedly stabilize under acidic conditions. 119 These findings suggest that N-nitroso-bile acids appear to be involved in the occurrence of EAC from Barrett's esophagus in patients with healthy acid-secreting stomachs.…”
Section: Activation Of Nf-κbmentioning
confidence: 78%
“…We developed not only EACs but also esophageal squamous cell carcinomas (ESCCs) in the rat reflux models (reflux model) . Our previous study also revealed that N ‐nitroso bile acid‐mutagenic derivatives of bile acids produced in vivo under highly acidic conditions could stimulate EAC . However, we also observed EACs in modified Levrat models with total gastrectomy suggesting that the tumors could be induced by exposure to unmodified nonmutagenic bile acids in the absence of gastric acid …”
Section: Introductionmentioning
confidence: 85%
“…We have studied the role of bile salts in the gut lumen when considering the pathogenesis and disease-promoting factors for experimental and clinical gastrointestinal diseases (25,26,(33)(34)(35)(36)(37). In the course of these investigations, it has been revealed that bile salts exhibit mainly cytotoxic but also certain stimulatory effects towards the intestinal epithelium (38).…”
Section: Discussionmentioning
confidence: 99%